From al-Jawāhir to Tafsir Ilmi: Interpreting Carbohydrates as a Source of Energy in the Qur’an - Kuswardani Dyah Ayu Kusumaningrum; Andri Nirwana; Muthoifin Muthoifin; Afra Kansa Maimuna (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
This article discusses the interpretation of Qur'anic verses about food and energy with a focus on carbohydrates from the perspective of Tafsir Ilmi of the Ministry of Religion of the Republic of Indonesia. The verses analyzed include Q.S. al-An'ām [6]: 95, Q.S. al-Mu'minūn [23]: 19, Q.S. Maryam [19]: 25, and Q.S. an-Naḥl [16]: 68–69, which allude to grains, fruits, dates, and honey as the source of human life. This study uses a qualitative method with a literature study approach and descriptive-analytical analysis of the Scientific Interpretation of the Ministry of Religion of the Republic of Indonesia, by comparing it in a limited way with classical and modern interpretations. The results of the study show that the Tafsir Ilmi of the Ministry of Religion of the Republic of Indonesia understands these verses by relating them to the findings of modern nutrition science, especially the function of carbohydrates as the main source of energy for the human body. Grains are understood as a source of complex carbohydrates, while dates, grapes, and honey are categorized as simple sources of carbohydrates that are easily digestible and quickly absorbed. The Scientific Interpretation does not make the Qur'an the basis for the formation of biochemical theories, but rather places science as a tool to affirm the function of food in the order of Allah's creation. Thus, the interpretation of Ilmi acts as a conceptual bridge between revelation and modern nutritional science, as well as showing methodological prudence in the integration of the Qur'an and science